Endometrial Câncer: Pelvic Control with only Externai Beam Radiotherapy Following Surgery Without Lymphnode Dissection - Faria, Sérgio Luiz (2022)
Median incidence of endometrial câncer in Brazil is of 6 new cases/100.000 women/year. Radiation therapy has been used as adjuvant treatment either pre or post surgery, given as teletherapy or brachytherapy or both. There is a consensus that FIGO stages II and III should receive pelvic irradiation, with or without brachytherapy. However most of such patients (>75%) have stage I câncer at diagnosis. Thus, there are prognostic subgroups depending on how deep the miometrium is invaded and the histologic grade ofthe tumor. Stage I câncer that invades more than 1/2 miometrium and/or is of high grade usually is also treated with adjuvante irradiation. Does the addition of intracavitary vault brachytherapy to externai beam radiotherapy (EBRT) result in improvedpelvic control? This question is yet to be accurately answered. In our Service, patients with endometrial câncer who have indication of adjuvant radiation have received only EBRT without brachytherapy, since 1990. Basic surgery for those patients has been a total abdominal hysterectomy and bilateral salpingo-oophorectomy without routine lymphnode dissection. We reviewed retrospectively 61 patients with endometrial câncer treated this way between 1990-95, with Cobalt, 4 fields, total dose of 45Gy-50.4Gy in 25 to 28 fractions. Median follow up of33 months showed only one pelvic (vaginal) relapse, 6/61 patients died and only one patient had moderate late bowel complication. Those results compare with others published in the literature.